Come and Knock on Our Door: Offenders' Perspectives on Home Visits Through Ecological Theory. (February 2018) - Patten, Ryan; La Rue, Emily; Caudill, Jonathan W.; Thomas, Matthew O.; Messer, Sarah
The use of home visits has a long and storied history in the United States from different disciplines, such as nursing, prenatal mothers, young families, health promotion, and community corrections. Ecological theory explains how formal actors play a role in the promotion in the health field through home visits, but does not address community corrections home visits. Through the use of 30 semi-structured interviews, this research seeks to expand the understanding of ecological theory by capturing the perceptions of offenders sentenced to home visits conducted by a sheriff's office. The findings suggest the participants supported the home visits by formal agents and, in general, the home visits created an atmosphere of respect between the participants and sheriff's office personnel. This study creates the context for future research to understand the role of formal agents in recidivism and evaluate the efficacy of home visits by community corrections agencies.